GEOLOGICAL AND HYDROGEOLOGICAL CONSIDERATIONS ON THE QUATERNARY DEPOSITS FROM CRIŞUL ALB BASIN, BETWEEN VÂRŞAND AND SEBIŞ (CLIMHYDEX PROJECT) - RADU E.; STANESCU GABRIELA; ROTARU CRISTIANA (Aerul şi Apa: Componente ale Mediului, 2015)
CLIMHYDEX project - "Extreme climate and the impact associated to the hydrological events from Romania" – is a Complex Project of Exploratory Research, supported by the Executive Agency for Higher Education, Research, Development and Innovation Funding. The overall objective of the project is to improve the knowledge on the quantification of the climate change impact on the hydrological and hydrogeological regime in extreme conditions, at river basin scale. The project runs in two pilot basins, Crişul Alb river basin and Bârlad basin. In the paper are presented geological and hydrogeological considerations on the Quaternary deposits from Crişul Alb basin, the sector between Vârşand and Sebiş. This data is based on the elaboration and interpretation of the hydrogeological cross-sections executed through the wells of the hydrogeological first order stations Vârşand, Chişineu Criş, Zărand, Ineu and Bocsig, and also on the hydrogeological mapping made in the area, in October 2012. The results will stand at the base of a future conceptual model for the elaboration of the groundwater flow mathematical model.